National trends in physical activity among adolescents in South Korea before and during the COVID‐19 pandemic, 2009−2021. Issue 2 (15th January 2023) - Kwon, Rosie; Koo, Min Ji; Lee, Seung Won; Choi, Yong Sung; Shin, Youn Ho; Shin, Jung U.; Koyanagi, Ai; Jacob, Louis; Smith, Lee; Rhee, Sang Youl; Kim, Hyug‐Gi; Min, Chanyang; et al.
Abstract: With the ongoing COVID‐19 pandemic, several previous studies from different countries showed that physical activity (PA) decreased during the COVID‐19 outbreak. However, few studies have examined the recent tendency of PA in the adolescent population. Thus, we aimed to investigate the long‐term trend of PA in Korean youth and the prevalence changes between before and during the COVID‐19 pandemic. Data from Korea Youth Risk Behavior Web‐Based Survey (KYRBS) was collected for consecutive years between 2009 and 2021. The period was separated into prepandemic (2009−2019), early‐pandemic (2020), and mid‐pandemic (2021). Self‐reported amount of PA was categorized into four groups (insufficient, aerobic, muscle strengthening, and both physical activities) according to World Health Organization (WHO) PA guidelines. A total of 840 488 adolescents aged 12−18 who fully responded to the survey were selected (response rate: 95.2%). The 13‐year trends in the proportion of adolescents who reported aerobic and muscle‐strengthening activities met or exceeded 2020 WHO exercise guidelines for adolescents plateaued (11.9% from 2009 to 2011, 14.2% from 2018 to 2019, 14.4% from 2020, and 14.0% from 2021); however, the slope decreased during the pandemic ( β diff, −0.076; 95% confidence interval [CI], −0.123 to −0.029). Proportion of sufficient aerobic exercise among adolescents sharply decreased midst the pandemic (28.0% from 2009 to 2011, 29.4% from 2018 to 2019, and 23.8% from 2020; β diff, −0.266; 95% CI, −0.306 to −0.226) but increased again in 2021 (26.0% from mid‐COVID 19; 95% CI, 25.4−26.7). Similar patterns were observed in Metabolic Equivalent Task (MET) score (MET‐min/week; 804.1 from 2018 to 2019, 720.9 from 2020, and 779.6 from 2021). The mean difference in MET score between pre‐COVID and post‐COVID was −55.4 MET‐min/week (95% CI, −70.5 to −40.3). Through a nationwide representative study, there was no significant difference with regard to the number of Korean adolescents who achieved the PA guidelines (pre and postpandemic); however, the prevalence of recommended levels of PA needs to increase more based on the trend before the COVID‐19 outbreak. The findings of this study suggest reinforcement of the importance of public health policies for Korean youths to be more physically active, especially during and after the pandemic.